Effects of a six-week multimodal training programme on the sprinting ability of adolescent rugby sevens players - Sastre-Munar, A.; Jimenez-Reyes, P.; Romero-Franco, N. (Journal of Sports Sciences, 2023)
This study evaluated the effects of 6-week multimodal training on the sprinting performance and biomechanics of adolescent rugby players. Twenty-four players were assigned to control group (CG) or intervention group (IG). For 6 weeks, CG maintained their training routine, while IG completed a training programme consisting of unresisted sprints, as well as heavy-resisted sprints, running technique drills and lumbopelvic stability. Before and after, sprint performance, horizontal force-velocity profile (FV-h), sprinting kinematics and spatiotemporal data were obtained. After the training, IG reduced the 0-5 m (p = 0.044), 0-10 m (p = 0.046) and 25-30 m (p = 0.035) split times compared with CG. In FV-h, IG displayed a higher maximal theoretical horizontal force (p = 0.035) and ratio of force (p = 0.048) than CG. Regarding kinematic and spatiotemporal variables, only IG improved step length (p < 0.001), step rate (p = 0.005) and distance between knees (p = 0.048) compared with baseline, but there were no between-group differences. Six weeks of multimodal training improved sprinting acceleration and mechanical variables of force application during sprinting of adolescent rugby players. Although IG improved some biomechanical variables compared with baseline, these changes were similar to those observed in CG.